2001
DOI: 10.1007/bf02723027
|View full text |Cite
|
Sign up to set email alerts
|

Mobius syndrome associated with ventricular septal defect

Abstract: We report a 10-year-old boy with Mobius syndrome (MS) associated with ventricular septal defect who was delivered after an unsuccessful curettage before the 10th week of gestation. Methylergobasine which is an ergot alkaloid was also applied during the curettage procedure. Despite of the curettage procedure, the pregnancy was continued and he was delivered. His developmental milestones were delayed. On account of this case, we think that direct mechanical fetal trauma and vasoconstriction or both may cause MS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…We believe that the close proximity of the face and heart in the early embryo (Jones, 2005), coupled with shared neural crest contributions to both developing regions (Kirby et al, 1983;Hutson and Kirby, 2003;Jones, 2005), may contribute to synchronous cardiac and facial malformations associated with oromandibuilar-limb hypogenesis spectrum, as well as other syndromes such as deletion 22q11 syndrome (velocardiofacial syndrome/DiGeorge syndrome), Noonan syndrome, fetal alcohol syndrome, and retinoid embryopathy syndrome. Patients with oromandibular-limb hypogenesis spectrum and intraoral softtissue bands (Purohit et al, 1989;Grippaudo and Kennedy, 1998) or cardiac anomalies have been reported (Caravella and Rogers, 1978;Bosch et al, 1984;Rarogue et al, 1988;Deda et al, 2001;Suvarna et al, 2006). It is interesting to note that intraoral synechiae associated with oromandibular-limb hypogenesis spectrum are often subglossopalatal (Purohit et al, 1989;Grippaudo and Kennedy, 1998), as was the case in the child reported in this study.…”
Section: Discussionsupporting
confidence: 66%
“…We believe that the close proximity of the face and heart in the early embryo (Jones, 2005), coupled with shared neural crest contributions to both developing regions (Kirby et al, 1983;Hutson and Kirby, 2003;Jones, 2005), may contribute to synchronous cardiac and facial malformations associated with oromandibuilar-limb hypogenesis spectrum, as well as other syndromes such as deletion 22q11 syndrome (velocardiofacial syndrome/DiGeorge syndrome), Noonan syndrome, fetal alcohol syndrome, and retinoid embryopathy syndrome. Patients with oromandibular-limb hypogenesis spectrum and intraoral softtissue bands (Purohit et al, 1989;Grippaudo and Kennedy, 1998) or cardiac anomalies have been reported (Caravella and Rogers, 1978;Bosch et al, 1984;Rarogue et al, 1988;Deda et al, 2001;Suvarna et al, 2006). It is interesting to note that intraoral synechiae associated with oromandibular-limb hypogenesis spectrum are often subglossopalatal (Purohit et al, 1989;Grippaudo and Kennedy, 1998), as was the case in the child reported in this study.…”
Section: Discussionsupporting
confidence: 66%
“…As the primitive otic and hypoglossal arteries regress and the vertebral arteries advance, inadequate blood supply to the cranial nerve nuclei may result in ischemia and malformation [20]. Conditions that may lead to attenuated blood flow include exposure to vasoconstrictive substances and maternal homocystinemia, which may cause subsequent ischemia of the hindbrain [12,23,[33][34][35][36][37][38]. Infection, hyperthermia, hypoxia, and vasculitis can also interfere with blood flow [16].…”
Section: Etiology and Geneticsmentioning
confidence: 99%
“…Other abnormalities include lingual hypoplasia, sensorineural hearing loss, craniofacial malformations (epicanthic folds, micrognathia), and abnormalities of the extremities (syndactyly, pes planus, valgus femur) [6,8]. Cardiovascular abnormalities are rarely present but can include dextrocardial, atrial, or ventricular septal defect, transposition of the great vessels, and total anomalous pulmonary venous connection [9][10][11][12][13]. Although most patients have normal intelligence, approximately 10 % of patients have mental retardation, and another 30-40 % may be diagnosed with autism [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Moebius y síndrome de Poland en un mismo paciente con exposición prenatal a misoprostol, confirmando un posible origen causado por un disruptor vascular. Adicionalmente se postula que, en el síndrome de Moebius, la regresión de la arteria primitiva del trigémino, que abastece el cerebro posterior antes de la generación de la arteria vertebral o basilar, puede afectar el desarrollo de los núcleos del nervio 5 .…”
Section: Caso Clínicounclassified